A Nutraceuticals with high antioxidant properties based on fruits and medicinal plants - Ziarati, Parisa; Tajik, Sepideh; Cruz-Rodriguez, Luis (Biological Environment and Pollution, 2023)
Recently, consuming natural food supplements derived from natural resources has become widespread in many developed societies due to the lack of side effects, low cost, and high antioxidant properties to prevent and treat many diseases. The research and formulation aimed to design a safe and effective medicinal and edible healthy natural nutraceutical with high antioxidant properties and rich mineral elements based on fruits and medicinal plants. Antioxidant, Protein, and inorganic contents of fruits and natural herbal plants were determined to evaluate the contents of active constituents of the meal in milligrams. The results were then used to formulate an edible herbal supplement as a solid oral system. The raw protein content of each ingredient was evaluated through the Kjeldahl method. The contents of the nutrient elements were measured in mg/kg (D.W) by ICP-Mass. All components were mixed thoroughly in some proper percentages, milled, and then dried by heating for 48 hours. The Flowability of the powder was subsequently evaluated using the work index and Hausner ratio. The work index of the sample was 34.3, and because the Flowability was not optimal, aerosol was added to 10 grams of a mixture of 1% by weight of the material. Finally, the working index reached 23, which is desirable. Furthermore, the ingredients were volumetrically encapsulated in OO-sized capsules and subjected to quality control tests. Performing organoleptic assays for controlling the physical and chemical properties of the formulation, the active ingredient was determined in terms of the results of Kjeldahl and inductively coupled plasma Mass spectrometry (ICP-Mass). The results of all control tests, including the weight deviation test, opening time test, and active ingredient dosage test, were conducted for the developed formulation according to credible pharmacopeia. According to the allowable daily dosages, the developed capsule is a proper herbal supplement with very high antioxidants.